2014
DOI: 10.1016/j.ijrefrig.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Reducing domestic food waste by lowering home refrigerator temperatures

Abstract: Domestic refrigerators often operate at temperatures which are higher than ideal for chilled food storage, with several studies finding averages around 7°C. Reducing temperatures for example to 4°C could significantly extend storage lives, giving greater opportunity for use before disposal. However, the savings in costs and emissions associated with reduced waste must be balanced against those associated with increased energy consumption at lower temperatures. Based on published storage lives of foods which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Few studies have addressed the effect of thermostat setting on energy consumption beyond acknowledging that reducing the thermostat setting will increase energy consumption. The energy consumption of fridge‐freezers is complicated by the fact that in most models, a single thermostat, sited in the refrigerator section, is used to control both the refrigerator and the freezer temperatures (Brown and others ). Adjusting this thermostat therefore affects not only the refrigerator temperature but also the freezer temperature, compounding the effect of temperature setting on energy consumption.…”
Section: Energy Consumption and Wastementioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have addressed the effect of thermostat setting on energy consumption beyond acknowledging that reducing the thermostat setting will increase energy consumption. The energy consumption of fridge‐freezers is complicated by the fact that in most models, a single thermostat, sited in the refrigerator section, is used to control both the refrigerator and the freezer temperatures (Brown and others ). Adjusting this thermostat therefore affects not only the refrigerator temperature but also the freezer temperature, compounding the effect of temperature setting on energy consumption.…”
Section: Energy Consumption and Wastementioning
confidence: 99%
“…Saidur and others () found that energy consumption in a fridge‐freezer increased by about 7.8% for every degree reduction in operating temperature. Brown and others () calculated that lowering refrigerator air temperatures from a mean of 7 to 4 °C would result in an annual energy consumption increase of approximately 14.1 to 36.8 kWh per refrigerator (depending on the type of refrigerator).…”
Section: Energy Consumption and Wastementioning
confidence: 99%
See 1 more Smart Citation
“…The refrigerators operated above 5.0ºC during 58% of the test, nevertheless representing a reduction of 2.0ºC compared to a similar study done two decades earlier. In fact, there are benefits in terms of storage live extend and consequently in food waste reduction reducing storage temperature of the refrigerator to 4ºC and promoting home freezing [6]- [8]. In an experimental study making use of temperature loggers placed at three shelf levels of 119 domestic refrigerators it was found that most users open the door around 20 times per day [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is known that the basic function of the refrigerator is storing fresh food and medicines, and this depends on the good performance of the refrigerator, which is closely linked to temperature distribution and air flow inside the compartments. Adequate temperature in these refrigerators could significantly extend the living cycle of food [3] and, inclusively, avoid the growth of certain types of bacteria [4]. In addition, the thermal behavior is influenced by the refrigeration system design, while the proper temperature distribution is achieved by a good interior design of the refrigerator.…”
Section: Introductionmentioning
confidence: 99%